Establishment and validation of an immune-related nomogram for the prognosis of pancreatic adenocarcinoma - Kan Wang; Yunkun Lu; Yanfei Cao; Ping Feng; Qiu Wu; Peng Xiao; Yimin Ding (Scientific Reports)
Abstract Pancreatic adenocarcinoma (PDAC) is a highly aggressive neoplasm characterized by limited therapeutic options, particularly in the realm of immunotherapy. This study aims to improve prognosis prediction to guide therapeutic decision-making, and to identify novel targets for immunotherapy of PDAC. We conducted Cox and LASSO regression analyses to develop immune-related gene signature and corresponding nomogram, and the robustness of these signatures was demonstrated using multiple approaches. Additionally, CIBERSORT, ESTIMATE, and xCell algorithms were utilized to assess immune cell infiltration, with experimental validation performed though qPCR. An immune-related gene signature consisting of 18 genes, and the prognostic nomogram was established with superior performance compared to the conventional staging system. Key parameters incorporated into the nomogram included the gene signature, tumor stage, and postoperative treatment. Patients identified as high-risk exhibited an anti-inflammatory tumor microenvironment, characterized by an increase in M2-like tumor-associated macrophages and heightened tumor purity. Notably, the expression of interleukin 6 receptor (IL6R) in PDAC was predominantly derived from macrophages and was significantly associated with patient survival outcomes. Furthermore, attenuated IL-6/IL-6R signaling was found to promote M2-like macrophage differentiation. This study successfully established an immune-related gene signature and a robust nomogram for predicting clinical outcomes in patients with PDAC. Furthermore, we identified IL6R as a promising target for future immunotherapeutic strategies.